2016
DOI: 10.1016/j.molcel.2016.10.019
|View full text |Cite|
|
Sign up to set email alerts
|

EPOP Interacts with Elongin BC and USP7 to Modulate the Chromatin Landscape

Abstract: Summary Gene regulatory networks are pivotal for many biological processes. In mouse embryonic stem cells (mESCs) the transcriptional network can be divided into three functionally distinct modules: Polycomb, Core and Myc. The Polycomb module represses developmental genes, while the Myc module is associated with proliferative functions and its mis-regulation is linked to cancer development. Here, we show that in mESCs the Polycomb Repressive Complex 2 (PRC2) associated protein EPOP (Elongin BC and Polycomb Rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
124
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(133 citation statements)
references
References 45 publications
7
124
0
Order By: Relevance
“…A recent study (Beringer et al, 2016) showed that EloB and EloC indirectly bind to PRC2 by associating with the BC-box containing, PRC2-auxillary factor EPOP (Liefke and Shi, 2015; Liefke et al, 2016). However, EloA was not found to be part of this complex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study (Beringer et al, 2016) showed that EloB and EloC indirectly bind to PRC2 by associating with the BC-box containing, PRC2-auxillary factor EPOP (Liefke and Shi, 2015; Liefke et al, 2016). However, EloA was not found to be part of this complex.…”
Section: Discussionmentioning
confidence: 99%
“…The complex is also part of a ubiquitin ligase complex along with Cullin5 and Rbx2 that drives degradation of stalled Pol II (Wilson et al, 2013). Two of the subunits of the Elongin complex have recently been linked to PRC2 via their interaction with the newly identified PRC2 interacting protein EPOP (Beringer et al, 2016; Liefke et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…ChIP experiments were performed by cross-linking ChIP as described 34 . In short, 100 million cells were crosslinked with 1% formaldehyde for 10 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…Promoter reads were counted from -2000 to +2000 relative to the transcription start site and normalized to reads per million (rpm). Following public data sets were used: SUZ12 (GSM700554, GSM700553), PHF19 (GSM700556, GSM700555) 10 , MTF2 (GSM415050) 12 , MRE-Seq (GSM881347) 29 , H3K4me3 (GSM2027596) 34 . CpG island and promoter definitions were downloaded from the UCSC browser.…”
Section: Methodsmentioning
confidence: 99%
“…For example, H2Bub1 is usually believed to be an active marker for gene transcription and results in an open chromatin context to facilitate gene transcription [14][15][16][17]. In addition to the establishing enzymes, multiple deubiquitinases have also been identified, including USP7 [22][23][24][25], USP12 [26], USP22 [27], USP44 [28], USP46 [26], and USP49 [29]. In addition to the establishing enzymes, multiple deubiquitinases have also been identified, including USP7 [22][23][24][25], USP12 [26], USP22 [27], USP44 [28], USP46 [26], and USP49 [29].…”
Section: Introductionmentioning
confidence: 99%